STUDI KASUS TINGKAT PEMOTONGAN DOMBA BERDASARKAN JENIS KELAMIN, KELOMPOK UMUR DAN BOBOT KARKAS DI TEMPAT PEMOTONGAN HEWAN WILAYAH MALANG - Syafrizal Muhammad; Gatot Ciptadi; Agus Budiarto (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
This research was conducted in private Slaughterhouses located in Ngunutsari Village on November 10th to December 10th, 2016. The purpose of this research is to know the level of the slaughtered sheep in the Malang. The sample used equals 105 sheep from of age less 1 to 4 years consisting of 12 rams and 93 ewes. The method used in this research is a case study. Research location was obtained by purposive sampling. Animals used in the research was selected by total sampling. Data observed was presented in average value and standard deviation for being descriptive analysis. Results showed that the level of sheep slaughtered in the age less than 1 year reached 31.43%, therefore the slaughtered of rams as much 1.9% and ewes 29.52% of the total slaughter. The level of ewe slaughtered has increased each week from 1st week 17.14%, 2nd week 16.2%, 3rd week 26.67%, and 4th week 28.57% in comparison with the Rams. The average of ram carcass weight from of age less 1 to 4 years in a row is 8.95 ± 0.07, 9.8 ± 2.68, 8.45 ± 0.63, 12.05 ± 3.6, and 20.64 ± 5.43 ± with level 10.66 ± 2.34 kg, whereas in the ewe is 6.99 ± 1.19, 7.26 ± 1.12, 8.21 ± 1.2, 12.01 ± 1.93, and 11.38 ± 3.29 with level 9.17 ± 2.35 kg. It was concluded that the level of slaughter reach 88.57% of ewe whiles the ram reach 11.43%. The level slaughter of sheep from of age less than 1 year reach 31.43% consists of the ram reach 1.9% and ewe reaches 29.52% of the total slaughter. Percentage of carcass of the sheep of age less than 1 year to 4 year in successive is 49,91%, 46,92%, 40,49%, 39,73%, 41,72% on Rams and 46,40%, 40,63%, 42,75%, 46,40%, 46,99% on Ewe..Keywords: Level Slaughter, Sheep, Slaughterhouse